Evaluation of electroacoustic devices by the equivalent scale methods - Toniasz ŁĘTOWSKI; Jacek SMURZYŃSKI (Archives of Acoustics)
This paper presents the preliminary results of experiments on the possibility of using methods based on the mutual masking of signals compared, in auditory evaluation. An attempt was made to objectivize the measure of the similarity of the signals, or the transmission channel quality, and to evaluate the degree of differentiation of objects investigated on an equivalent physical scale. In the preliminary experiments a number of experimental procedures were examined, two of which, characterized by the relatively highest differentiation sensitivity, underwent more detailed evaluation. The results indicated the possibility of objectivizing the measure of the transmission circuit quality in the range of frequency response variation over a third-octave.